Professional SharePoint® 2010 Branding and User Interface Design - Drisgill, Randy; Ross, John; Sanford, Jacob; Stubbs, Paul; Riemann, Larry (Wrox, 2010)
A must have guide for creating engaging and usable SharePoint 2010 branding With SharePoint 2010, Microsoft has provided a more robust environment for creating collaboration and content management sites that rival any of the popular websites on the internet. Creating a branded SharePoint site involves understanding both traditional web design techniques as well as topics that are typically reserved for developers. This book bridges that gap by not only providing expert guidance for creating beautiful public facing and internal intranet sites but it also addresses the needs of those readers that only want to understand the basics enough to apply some style to their sites. Things like creative design, the experience visitors have navigating your user interface, ease of use, these are all important branding considerations and not always intuitive. This unique book from a team of SharePoint branding experts lays it all out. The book is divided into four sections: Introduction to SharePoint Branding: In this part you will learn about what SharePoint branding is and how the topic has changed since SharePoint 2007. Branding Basics: This section is geared towards both getting started as well as being a guide for people that don't want to dive super deep into the advanced topics of SharePoint branding. You will learn about how to plan for branding projects, including creating wireframes and creative mockups as well as gathering requirements and estimation. You will learn how to work with SharePoint Designer 2010, SharePoint 2010 themes, and SharePoint navigation as well as gain an understanding of the low and medium effort approaches to branding can be used to make SharePoint look more like your own visual style. Advanced Branding: This is where you will learn about the more intricate techniques for making large changes to the SharePoint UI, such as cascading style sheets (CSS), master pages, page layouts, web parts and XSLT. You will also get an introduction to deploying SharePoint branding to production servers using solution packages (WSP). Other Topics: Everything else that is related to SharePoint branding is discussed here, including working with the SharePoint 2010 ribbon and client side technologies such as the client object model, jQuery, and Silverlight. Whether you want to make SharePoint look completely different or just make minor design changes, this expert guide will provide tips, techniques, and insights to get the job done.